2009
DOI: 10.1111/j.1740-0929.2008.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

The comparative study digestion and metabolism of nitrogen and purine derivatives in male, Thai, Swamp buffalo and Thai, Brahman cattle

Abstract: Studies on in vivo digestion, rates of passages, metabolism of nitrogen, urinary purine derivative excretion and blood metabolites were carried out in Thai Brahman cattle and Thai swamp buffaloes (16 months old). The animals were fed mixed diets based on pineapple (Ananas comusus) waste silage containing urea-N (NPN) and true protein from a concentrate (TP). The Brahman cattle (310 +/- 15 kg) were heavier than the swamp buffaloes (195 +/- 9.4 kg) and had higher dry matter (DM), organic matter (OM) and neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
2
2
Order By: Relevance
“…It is to be expected that the fermentation pattern in the rumen probably is different when animals are being fed RTP. However, glucose concentration of 72.9-77.0 μmol/ml in the plasma of Brahman cattle in the present study was lower than the range of 78.3-110 μmol/ml observed by Jetana et al (2006;2009) in Brahman cattle.…”
Section: Effects On Blood Metabolitescontrasting
confidence: 86%
See 1 more Smart Citation
“…It is to be expected that the fermentation pattern in the rumen probably is different when animals are being fed RTP. However, glucose concentration of 72.9-77.0 μmol/ml in the plasma of Brahman cattle in the present study was lower than the range of 78.3-110 μmol/ml observed by Jetana et al (2006;2009) in Brahman cattle.…”
Section: Effects On Blood Metabolitescontrasting
confidence: 86%
“…This effect of high sugar in RTP, subsequently resulted in the concentration of insulin in the plasma being increased to control glucose metabolism. The range of plasma insulin concentrations of 13.6-22.2 μ.i.u./ml in the present cattle was higher than the range of 8.40-16.6 μ.i.u./ml observed in animals by Jetana et al (2006;2009). It is to be expected that the fermentation pattern in the rumen probably is different when animals are being fed RTP.…”
Section: Effects On Blood Metabolitescontrasting
confidence: 70%
“…The level of digestibility observed in groups FR and C are in line with those reported by other authors. Jetana et al (2009) in a study on the digestion and metabolism of nitrogen and purine derivatives observed that the coefficient of digestibility of organic matter was 0.78 and 0.80 in buffaloes and cattle, respectively. Another comparative study on buffaloes and sheep reported digestibility coefficients of 66.68% v. 64.32%, respectively (Bartocci and Terramoccia, 2006).…”
Section: Behaviour and Puberty Of Buffalo Heifersmentioning
confidence: 99%
“…Chanthakhoun et al ( 2012 ) reported higher ability of swamp buffalo than cattle in digesting low-quality roughages, and this might be due to the higher number cellulolytic bacteria ( Ruminococcus albus ) in buffalo rumen. Jetana et al ( 2009 ) demonstrated that Brahman cattle were better fi bre utilizer than swamp buffaloes when fed on pineapple waste silage.…”
Section: Digestion Of Feeds In the Rumenmentioning
confidence: 98%